2020
DOI: 10.1007/s12144-020-00919-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of individual personality in conceptualizing and measuring group characteristics

Abstract: In previous research, group characteristics have often been measured without taking the individual perspective of the group members into account. Therefore, the influence of individual personality (and other individual-level characteristics) on group characteristic ratings beyond the influence of the actual group remains largely unexplored. Additionally, some studies use group means of individual personality as group characteristics, however, evidence for interrelations or differences between these approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…As explained in the method section, we split the analyses for each variable into one analysis for the individual-level predictors and another for the team-level predictors. These analyses can be compared in terms of significance and effect size (explained slope variance) because the variables used in each are highly unlikely to be intercorrelated: Past research has shown that calculating team-level variables using the procedure applied here causes them to be independent of the characteristics of the individuals rating them (Deckers et al, 2020)-in other words, intercorrelations, which are the main reason why comparisons between different models are usually not permissible (Hox et al, 2017;Judd et al, 2017), likely do not play a role here. Together, the results that no significant interactions were found for the individual HEXACO domains and no slope variance was explained by them, yet significant interaction effects were found for some team characteristics and these were able to explain slope variance, lead us to conclude that team characteristics play a larger (but, as mentioned, still rather limited) role in predicting training transfer in this specific context than individual personality does.…”
Section: Summary Of Goals and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As explained in the method section, we split the analyses for each variable into one analysis for the individual-level predictors and another for the team-level predictors. These analyses can be compared in terms of significance and effect size (explained slope variance) because the variables used in each are highly unlikely to be intercorrelated: Past research has shown that calculating team-level variables using the procedure applied here causes them to be independent of the characteristics of the individuals rating them (Deckers et al, 2020)-in other words, intercorrelations, which are the main reason why comparisons between different models are usually not permissible (Hox et al, 2017;Judd et al, 2017), likely do not play a role here. Together, the results that no significant interactions were found for the individual HEXACO domains and no slope variance was explained by them, yet significant interaction effects were found for some team characteristics and these were able to explain slope variance, lead us to conclude that team characteristics play a larger (but, as mentioned, still rather limited) role in predicting training transfer in this specific context than individual personality does.…”
Section: Summary Of Goals and Resultsmentioning
confidence: 99%
“…When examining the team characteristics, we also sought to compare the direct and indirect approaches to conceptualising and measuring these team characteristics (for an overview, see Deckers et al, 2020). In this study, we found evidence for the importance and merit of both approaches-both team-level means of individual personality characteristics and team-level means of team characteristic ratings were found to influence training transfer (and were also associated with differences in psychological strain cross-sectionally).…”
Section: Implications For Conceptualisations Of Group-level Character...mentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research provides robust evidence suggesting that team composition and teambuilding are essential determinants of team performance. Demographic diversity and team-level abilities have been linked to team processes such as team members' cohesion and helping behavior (Michael Holmes Jr. et al, 2021), team conflicts (Jones et al, 2019), communication (Deckers et al, 2020;Keller, 2001), and coordination (Dahlin, Weingart, & Hinds, 2005), team creativity (Pirola-Merlo & Mann, 2004;Taggar, 2002).…”
Section: Discussionmentioning
confidence: 99%